Assessment of body composition in children with chronic renal failure - Schaefer, Franz; Wühl, Elke; Feneberg, Reinhard; Mehls, Otto; Schärer, Karl (Pediatric nephrology, 2000)
In children with chronic renal failure treated conservatively by dialysis or by transplantation, various alterations of the nutritional, metabolic and fluid homeostasis may occur that may critically affect the patients’ acute and chronic well-being. In the past, the assessment of body composition in children was hampered by insufficient precision, standardization and/or availability of appropriate anthropometric tools. Recently, there have been several methodological advances that may facilitate close and precise monitoring of body composition in this population. Specifically, the use of body mass index (BMI) data in children has become possible by the introduction of pediatric reference values processed for the calculation of standard deviation scores accounting for the skewed distribution of BMI. Skewness-adapted reference data have also been provided for percentage fat mass as assessed by multisite skinfold measurements. In addition, bioelectrical impedance analysis has been validated in healthy children as well as in pediatric dialysis and renal transplant populations. This novel auxological technique provides a highly reproducible, non-invasive and inexpensive way of assessing changes in total body water content in dialysed patients, as well as changes in fat and fat-free mass prior to dialysis and after renal transplantation.
Gesehen am 11.01.2021